Indonesian Legal Protection for Consumers on the Validity of Electronic Contracts in the E-Commerce Transactions - Iftinaity Shaumi Rahma; Hasiana, Eliza July; Cantika, Sian Lie; Octaviona, Tania (Universitas Airlangga, 2022)
Currently, internet development grows rapidly which facilitates and eases various economic activities, especially e-commerce transactions, on a global scale. In 1996, the UNCITRAL regulated the e-commerce transactions, including e-contracts. The e-contract is one of the most relevant matters in e-commerce transactions, especially it is of importance for the consumers to avoid any unwanted situations. However, several problems arise for consumers in conducting e-commerce transactions, such as the asymmetrical bargaining power of the parties involved. In this sense, there is an urgency for the legal protections for consumers. The objective of this article is to understand the connection between consumers' legal protection and e-contracts validity in e-commerce transactions. The research method used is the legal descriptive analysis through statutory and conceptual approach. This study analyzes the legal relationship between the legislations related to the e-contracts within e-commerce transaction in Indonesia, which are the Indonesian Civil Code, Law Number 8 of 1999 concerning Consumer Protection, and Law Number 19 of 2008 on Information and Electronic Transactions. Through a systematic appraisal, it argues that the current legal framework does not fully guarantee legal certainty for consumers in e-commerce transactions, such as on the obligations of producers and distributors to customers in the e-commerce transactions.